2015
DOI: 10.4103/1995-705x.172195
|View full text |Cite
|
Sign up to set email alerts
|

A community-based cross-sectional study of cardiovascular risk in a rural community of Puducherry

Abstract: Background:The World Health Organization (WHO) / International Society of Hypertension (ISH) risk prediction chart can predict the risk of cardiovascular events in any population.Aim:To assess the prevalence of cardiovascular risk factors and to estimate the cardiovascular risk using the WHO/ISH risk charts.Materials and Methods:A cross-sectional study was done from November 2011 to January 2012 in a rural area of Puducherry. Method of sampling was a single stage cluster random sampling, and subjects were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…(2015),[ 12 ] and Shrivastava et al . (2015)[ 19 ] documented similar results with majority of the patients falling under low-risk (<10%) category for CVDs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…(2015),[ 12 ] and Shrivastava et al . (2015)[ 19 ] documented similar results with majority of the patients falling under low-risk (<10%) category for CVDs.…”
Section: Discussionsupporting
confidence: 52%
“…In contrast to this, Shrivastava et al . (2015)[ 19 ] documented in their study that maximum (36.2%) of the diabetics had high (≥20%) CVD. This disparity might be because of differing socio-demographic profile, family history of CVD risk factors, and dietary habits among the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…This was relatively higher as compared to another carried out in Group C employees in Puducherry where only 4% individuals with CVD risk >10% [15]. Another community based cross sectional study in Puducherry found 17% participants with CVD risk >30% [18].Internationally, a study carried out in three Asian countries found high CVD risk in 6%, 2.3% and 1.3% study participants in Mongolia, Malaysia and Cambodia respectively [19].…”
Section: Discussionmentioning
confidence: 73%
“…Sample size-Sample size was calculated using Epi Info TM 7. Sample size calculated for estimation of CVD risk for 99% confidence interval, with an acceptable deviation of 10%, at an expected frequency of 20% was 106 [18]. However, a total of 116 individuals were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study conducted in Puducherry, reported that 17% of subjects had moderate to high risk of developing CVD in next 10yrs. 7 With 5% allowable error and using formula 4pq/ d 2 the sample size derived as 225. Totally, 230 study participants were involved in the study using simple random sampling method to select the households for the study.…”
Section: Methodsmentioning
confidence: 99%